An examination of three Black African male mathematics teachers' teacher preparation and teaching experiences in Africa and the USA. Issue 2 (11th June 2018) - Davis, Julius L.
Abstract : Purpose: There is very little research of Black male mathematics teachers from African countries teaching in the USA, specifically, their preparation and teaching experiences. The purpose of this study is to shed light on three Black male mathematics teachers from two African countries teacher preparation and teaching experiences in three African countries and the USA.teachers. Design/methodology/approach: This study used a qualitative narrative research design to examine the teacher preparation and teaching experiences of Black African male mathematics teachers. Findings: The results of this study reveal that the Black African male mathematics teachers participated in traditional and alternative teacher preparation programs that were unique to the African countries. The results also revealed that these teachers saw their teacher preparation program in the USA as preparing them to teach in this context. The results also revealed that all three of the teachers' experienced success teaching struggling learners and English language learners mathematics in African countries and the USA. Research limitations/implications: This study is limited to a small participant pool of three Black African mathematics teachers that cannot be generalized to other Black male teachers. There needs to be more research of Black male mathematics teachers, in general, and those from other countries, specifically. There also needs to be more research of Black male teachers' teaching practices that are successful with Black students as well as English language learners. Practical implications: Based on the study findings, policy-makers and stakeholders interested in recruiting and retaining Black male teachers and specifically, in mathematics needs to expand conceptualization and definitions to include those from other countries. Originality/value: This results of this study add a valuable contribution to the research of Black male teachers, in general, and mathematics, in particular. It expands conceptualizations of who constitutes a Black male teachers in the USA.